2021
DOI: 10.1186/s12902-021-00890-8
|View full text |Cite
|
Sign up to set email alerts
|

Providing lifestyle advice to women with PCOS: an overview of practical issues affecting success

Abstract: Polycystic Ovary Syndrome (PCOS) is a common endocrine disorder affecting up to 13 % of women. Lifestyle interventions are first-line treatments, however attrition in women with PCOS is high. This review summarises current evidence on barriers to lifestyle management in PCOS and suggested strategies for overcoming these challenges, mapped to the Capability, Opportunity, Motivation and Behaviour model.Physical capability for lifestyle changes may be impacted by altered gut hormone regulation and energy expendit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 138 publications
0
25
0
Order By: Relevance
“…According to our analysis, from the perspective of the socio-demographic profile, we concluded that marital status, education, financial background, area of residence, smoking habit, and family history of PCOS might be responsible for developing mental health issues among our participants. Therefore, an earlier study suggested that lifestyle change can be an option for the effective management of PCOS [ 49 ]. Another study revealed environmental and lifestyle factors contributing poor mental health of patients with PCOS [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our analysis, from the perspective of the socio-demographic profile, we concluded that marital status, education, financial background, area of residence, smoking habit, and family history of PCOS might be responsible for developing mental health issues among our participants. Therefore, an earlier study suggested that lifestyle change can be an option for the effective management of PCOS [ 49 ]. Another study revealed environmental and lifestyle factors contributing poor mental health of patients with PCOS [ 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the decrease in sitting behaviour minutes, which in the SMS+ group amounted to several hours a day, may also be seen as a significant improvement. One could hypothesize that the above-mentioned findings do count as clinically relevant in this population of women with PCOS in which lifestyle habits are known to be difficult to improve [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…At present, lifestyle change that is centered on weight reduction, combined with symptomatic treatment, is dominant. However, women with PCOS face several hurdles to successful lifestyle change, such as reduced metabolic flexibility, lack of intrinsic motivation, negative body image, depression, eating disorders, and altered risk perception [ 4 , 5 ]. Linking PCOS to inherited insulin resistance that is frequently aggravated by obesity-induced insulin resistance paved the way for trials of diabetes drugs in PCOS [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%